Storytelling and the Humanbecoming Family Model. (April 2022) - Bunkers, Sandra Schmidt; Flinn, Elizabeth; Letcher, Deborah; Reding, Noreen; Damgaard, Gloria; Young, Linda; Klein, Linda; Knitig, Kathy
The authors in this article will present storytelling through the lens of the humanbecoming family model. From this perspective, storytelling can be viewed as the following: (a) family storytelling as a mode of fostering personal and family becoming, (b) family storytelling as a confirming of family beliefs and values, and (c) family storytelling as a way of addressing issues of grief and loss. Selected literature is presented to highlight the essences, paradoxes, and processes of the humanbecoming family model.